The Value of Biomarkers in the Diagnosis and Prognosis of Heart Failure in Older Age - V. N. Larina; V. I. Lunev (Архивъ внутренней медицины)
The search for reliable algorithms for diagnosing heart failure with preserved left ventricular ejection fraction (LVEF) in elderly patients is an urgent problem due to the low specificity of clinical manifestations and the peculiarities of involutive processes occurring in the human body. As an alternative diagnostic approach, it is possible to determine in the blood laboratory biochemical markers — a promising method of diagnosis, prognosis and control of the effectiveness of treatment. The article examines the significance of myocardial stress markers (brain natriuretic peptide, N-terminal brain natriuretic peptide, median fragment of atrial natriuretic peptide); «mechanical» myocardial stress (soluble stimulating growth factor expressed by gene 2 — sST2), copeptin, galectin-3 in patients with heart failure and preserved LVEF, including older persons, as well as the possibility of their use in outpatient practice to predict the course of heart failure. The contribution of the multimarker model for a comprehensive assessment of prognosis is discussed, taking into account both the «hemodynamic» side of myocardial stress (pressure or volume overload, markers — natriuretic peptides), and «mechanical» (fibrosis / hypertrophy / heart remodeling, marker — sST2) myocardial changes.